AB0283 Dermatologic adverse events in a cohort of patients with rheumatoid arthritis using anti-tnf therapy in a real-life setting. (23rd January 2014) - Real, A. P.; Palomino, A.; Villarreal, L.; Bello, J.; Santos-Moreno, P.
Abstract : Background: Biological therapy is a major therapeutic tool to prevent clinical and radiological progression of rheumatoid arthritis (RA). On the other hand, adverse effects of these medications are a problem in clinical practice. Objectives: The aim of this study was to describe and compare the most frequent dermatologic adverse events with the use of biologic anti-TNF therapy in patients with RA in a real-life ambulatory setting. Methods: A descriptive study was done. A review of dermatological adverse event reports presented in pharmacovigilance committee was completed monthly during last 12 months in a specialized in RA center in Colombia. Descriptive epidemiology was used, percentages and averages were calculated. Results: 357 patients were using biological therapy in a cohort of 1678 RA patients last 12 months. Were 314 women (87.9%) and 43 (12.1%) men. Mean age 56.4 years old. In 31 (8.7% of all) patients were reported dermatologic adverse events (AE); AE were categorized according WHO classification in mild, moderate and severe; between them 14 (45.2%) were mild, 17 (54.8%) were moderate and none were severe. From 31 events reported, only 7 (22.6%) were biopsied and the other 24 cases were not clarified what type of dermatologic reaction presented (77.4%). For time of presentation, in first 15 days were informed 8 AE (25.8%), between 15 to 30 days were 6 (19.4%) AE, and more than 30 days were reported 17 (54.8%) AE. Regarding therapeutic approach in 5 patients (16.1%) biologic was temporarily suspended, in 14 (45.2%) was permanently withdrawn and patients were switched to another biological, and 12 (38.7%) patients were followed for drug and reactions surveillance. Concerning to type of biologic in 29 patients (93.5%), dermatologic adverse events were with anti-TNF therapies. Conclusions: Dermatological adverse events using biologics founded in patients of a specialized RA center are similar to those reported in literature; Biological therapy is considered a safe and recommended treatment for management of RA. Dermatologic AE were more mostly common with anti-TNFs therapies. Disclosure of Interest: None Declared